The effect of edible coatings on the nutritional quality of 'Bravo de Esmolfe' fresh-cut apple through shelf-life. (January 2017) - Guerreiro, Adriana C.; Gago, Custódia M.L.; Faleiro, Maria L.; Miguel, Maria G.C.; Antunes, Maria D.C.
Abstract: The effect of edible coatings in combination with anti-browning agents on fresh-cut 'Bravo de Esmolfe' apple was studied. Four formulations of edible coatings were used: sodium alginate (AL) at 2% (w/v) with either eugenol (Eug) 0.1% (w/v) or Eug 0.1% + citral (Cit) 0.15% (w/v) and pectin (PE) 2% (w/v) with Eug 0.2% or Cit 0.15%. Three anti-browning agents were used: ascorbic and citric acids at 1% (w/v) and sodium chlorite at 0.05% (w/v). Fresh-cut apples were immersed into those solutions and then stored at 4 °C. On days 0, 2, 4, 6 and 8, samples were taken to perform physicochemical and biochemical analysis (browning index, firmness, weight loss, microbial growth, taste panels, total phenols, flavonoids, sugars content, antioxidant activity and ethylene production). The AL edible coatings performed better than the PE in reducing the browning index. Edible coatings improved the shelf-life of fresh-cut apple by reducing microbial spoilage without significantly affecting sensory and nutritional qualities. The anti-browning agents further increased this capacity, with ascorbic acid performing best. Based on general and sensory quality characteristics, fresh-cut apples appeared to be better preserved with AL 2% + Eug 0.1% plus dipping in ascorbic acid 0.1%. Highlights: Study of edible coatings with anti-browning agents on fresh-cut 'Bravo de Esmolfe' apple. Effect of edible coatings and anti-browning agents on sensory and nutritional attributes. Fresh-cut 'Bravo de Esmolfe' apple shelf-life. Coatings and anti-browning agents maintained most quality attributes. The use of the edible coatings can be considered as safe and effective treatment.